Synthesis of sculpture and architecture in the last third of the 20th — early 21st century: typology of artistic communication options - Gildina Tatiana A.; Podol’skaya Kseniya S. (Архитектон)
The article considers the development of a typology of variants of synthesis of sculpture and architecture in the last third of the 20th — early 21st century. Changes in the morphological properties of sculpture and architecture have actualized the issue of development of methods of synthesis of these types of art. We identified the features of artistic synthesis of sculpture and architecture in historical development and at the current stage through analysis of morphological features of contemporary architectural and sculptural forms against the benchmark works of art and defined the main types of synthesis of architecture and sculpture at the present stage. This research work meets the current need for a typology of methods of artistic communication between genres of art and approaches to their study and for updated terminology used in the analysis of contemporary artistic processes. It also responds to the challenge of updating the contents of the programs of academic disciplines related to the study of current artistic practices in the system of art education.